All Days 2010
DOI: 10.2118/127489-ms
|View full text |Cite
|
Sign up to set email alerts
|

Remedial Sand Consolidation: Case Study From Mahakam Delta, Indonesia

Abstract: Tunu and Tambora gas fields are located in the Mahakam river delta in the province of East Kalimantan, Indonesia. The fields consist of wet gas bearing sand bodies over a height of 13000 ft. The main producing zones are developed by intensive drilling with wells simply completed to allow a bottom up perforation strategy. The main objective is gas production from the deeper Main Zone layers. The shallow reservoirs prone to sand production are not primarily targeted. When sand production after additional perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…EICP can be utilized to solve sand production issues. For this process to be applicable, certain criteria have to be considered, and many researchers have supported that the following criteria should be considered before choosing chemical sand consolidation as a sand control method ( Carlson et al, 1992 ; Wasnik et al, 2005 ; Chaloupka et al, 2010 ; Renpu, 2011 ). The bottom-hole temperature range has to be considered; in general, a range between 100 and 225°F is applicable.…”
Section: Discussionmentioning
confidence: 99%
“…EICP can be utilized to solve sand production issues. For this process to be applicable, certain criteria have to be considered, and many researchers have supported that the following criteria should be considered before choosing chemical sand consolidation as a sand control method ( Carlson et al, 1992 ; Wasnik et al, 2005 ; Chaloupka et al, 2010 ; Renpu, 2011 ). The bottom-hole temperature range has to be considered; in general, a range between 100 and 225°F is applicable.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental investigation, conducted by the researchers, showed that the compressive strength was 1340 psi at temperature up to 204 ℃ [55]. Chaloupka et al [56] applied catalyzed epoxy fluid to consolidate a sand formation in the Mahakam river delta, Indonesia. They reported that the regained permeability is 63% at the temperature range of 93-177 ℃, [56].…”
Section: Epoxy Resinmentioning
confidence: 99%
“…Chaloupka et al [56] applied catalyzed epoxy fluid to consolidate a sand formation in the Mahakam river delta, Indonesia. They reported that the regained permeability is 63% at the temperature range of 93-177 • C, [56].…”
Section: Epoxy Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…A research is required for the treatment of such problems in Mawar Field. Based on the observation, two wells in the field were decided to get chemical treatment [4,5]. The data of the wells are given in Table 1.…”
Section: Figure 1 Ipr Curve Of X-1 Wellmentioning
confidence: 99%